ByzRev 04.2022.012: Klaas Bentein – Mark Janse (eds), Varieties of Post-Classical and Byzantine Greek: (Trends in Linguistics. Studies and Monographs 331). Berlin: De Gruyter – Mouton 2021. - Signes Codoñer, Juan (The Byzantine Review, 2022)
Klaas Bentein – Mark Janse (eds), Varieties of Post-Classical and Byzantine Greek (Trends in Linguistics. Studies and Monographs 331). Berlin: De Gruyter – Mouton 2021. XVIII, 429 pp. – ISBN 978-3-11-060855-7 (€ 99.95)